The Obstacles and Strategy of Project Based Learning Implementation in Elementary School - Nyai Cintang; Dewi Liesnoor Setyowati; Sri Sularti Dewanti Handayani (Intelektual Pustaka Media Utama, 2018)
This study aims to: 1) examine the challenges teachers encounter in implementing project-based learning in 2013 curriculum, 2) to examine teachers’ strategies in integrating project-based learning in 2013 curriculum. This research finds several obstacles faced by teachers and strategies that can be done in the implementation of project-based learning, they are: 1) the obstacle in terms of students' capability can be overcome by familiarizing them to complete projects; 2) the obstacle in terms of indiscipline can be solved by optimizing the teacher's role as supervisor; 3) the time constraint is overcome by some alternative ways; 4) the obstacle in terms of equipment availability is addressed by modifying projects; 5) the obstacle in terms of student's inequality is overcome by forming propori sembang group; 6) the cost issues are resolved by using classroom cash or selecting projects suitable for the available resources. Another positive finding is that teachers should have the confidence and commitment in implementing project-based learning. Based on these results, it can be concluded that most teachers and even experienced teachers will experience difficulties and challenges when trying to implement project-based learning. However, experienced teachers have strategies to overcome obstacles, thus project-based learning can still be implemented.